Restricted immunoglobulin VH usage and VDJ combinations in the human response to Haemophilus influenzae type b capsular polysaccharide. Nucleotide sequences of monospecific anti-Haemophilus antibodies and polyspecific antibodies cross-reacting with self antigens. - Adderson, E E (1993)
To examine the human antibody repertoire generated against a biologically significant antigen we have obtained sequences of heavy chain variable region genes (IgVH) from 15 monoclonal antibodies specific for the capsular polysaccharide of Haemophilus influenzae type b (Hib PS). All VH segments are members of the VH3 family and 9 of 15 are members of the smaller VH3b subfamily. Restriction is evident by the shared use of certain VDJ joints in independent hybridomas from different subjects. Two hybridomas generated from the same subject demonstrate identical heavy chain variable region gene sequences but differ in isotype and rearrange alternative light chain variable region genes (IgVL), suggesting that in a normal immune response, a single pre-B cell clone may use different light chain rearrangements and give rise to progeny capable of reacting with antigen. Using a polymerase chain reaction assay optimized to detect base pair differences among VH genes we demonstrate that at least a portion of expressed anti-Hib PS VH genes have undergone somatic mutation. Anti-Hib PS heavy chain genes are homologous to VH segments encoding autoantibodies and two hybridomas secrete anti-Hib PS antibody that cross-reacts with self antigens (double-stranded DNA and single-stranded DNA). Comparison of VH regions of self-reactive and monospecific anti-Hib PS Ab demonstrates no consistent structural feature correlating with fine antigen specificity. These data demonstrate significant restriction in VH usage and VDJ recombination in the anti-Hib PS response and confirm that autoantibodies may be elicited during normal immune responses.